Two new species of the genus Nosphistica Meyrick (Lepidoptera, Lecithoceridae, Lecithocerinae) from China, with a checklist of the world - Yu, Shuai; Wang, Shuxia (Zootaxa, 2024)
Two new species of the genus Nosphistica Meyrick, 1911 from China are described as new: N. eucalla sp. nov. and N. longiclavata sp. nov. Images of adults and genitalia for the newly described species and a checklist of the genus are given.